(untitled) (CIPEEX, 2025)
The Legal Sociology investigates the connections between law and society, being an interdisciplinary discipline. Its main objective is to reveal how legal principles are shaped by various social factors. The use of qualitative and quantitative methods allows an in-depth examination of these interactions. Legal sociology demonstrates that law is dynamic, influenced by historical, cultural and political factors. Laws are built from the needs, values and power relations of the society in which they are inserted. By adopting a sociological approach, law scholars transcend a purely normative view, considering the social, cultural and political contexts that influence the production and application of laws. This enriches the legal debate and makes room for the construction of a fairer, more inclusive system that is sensitive to the needs of society. Reflecting on the contributions of Legal Sociology in the light of the ideas of Pedro Demo, reinforces the importance of an interdisciplinary and contextualized approach to a more complete understanding of law and its function in contemporary society.